A wireless shortwave near-field probe for monitoring structural integrity of dielectric composites and polymers. (June 2018) - Kumar, Deepak; Karuppuswami, Saranraj; Deng, Yiming; Chahal, Premjeet
Abstract: In this paper, a passive wireless sensor is presented for monitoring structural integrity of wind turbine blades manufactured using reinforced glass fibers. The sensor developed is an Inductor Capacitor (LC) based resonant tank that detects the defects in the near-field region. The sensor is designed such that, strong electric fields exist along the near-field region of the capacitor allowing detection of very small change in effective dielectric constant of the target. The sensitivity of the developed RF sensor is verified by shortwave imaging of the target. The designed sensor has multiple reuse capability and is used in the real-time monitoring of defects along the manufacturing supply chain. A path to two-dimensional simultaneous scanning of target is shown by demonstrating a multiple LC tank array probe. The details of single and array probes for detection of fiber defects are outlined in the paper.